Analysis of Forecasting Methods and Models (Eurasian Journal of Engineering and Technology, 2022)
Technological processes (TP) of formalin production are characterized by continuity, toxicity of raw materials, product and exhaust gases, fire and explosion hazard, a large number of interrelated input and output parameters, drift of parameters of the formaldehyde synthesis stage, and a long residence time of absorbed components in absorption apparatuses. The main mode of operation of formalin production units is static.